2008
DOI: 10.1085/jgp.200810103
|View full text |Cite
|
Sign up to set email alerts
|

Local Anesthetics Disrupt Energetic Coupling between the Voltage-sensing Segments of a Sodium Channel

Abstract: Local anesthetics block sodium channels in a state-dependent fashion, binding with higher affi nity to open and/or inactivated states. Gating current measurements show that local anesthetics immobilize a fraction of the gating charge, suggesting that the movement of voltage sensors is modifi ed when a local anesthetic binds to the pore of the sodium channel. Here, using voltage clamp fl uorescence measurements, we provide a quantitative description of the effect of local anesthetics on the steady-state behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 45 publications
6
77
0
Order By: Relevance
“…4). This finding is consistent with evidence for stabilization of the depolarized up state by LAs (33,35).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…4). This finding is consistent with evidence for stabilization of the depolarized up state by LAs (33,35).…”
Section: Resultssupporting
confidence: 91%
“…At a level just below fenestrations and between S5/S6 and the VSD, BZC binds to aromatic pocket site F b , created by F107(S4), F140(S5), and F207(S6). This site may help explain block by voltage-sensor inhibition, suggested to occur close to FS6, restricting the bottom of the PD and S4-S5 linker, reducing the effect of voltage on the activation gate (15,33,34). Even more directly influencing activation, low-affinity site G b involves H-bonding to N49 and interaction via cation-π to the voltagesensing R102 (S4; see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally appreciated that sodium channel inhibitor action involves a number of different mechanisms 12 including pore block 13 , electrostatic interactions between the cationic charge on the drug and sodium ions at the selectivity filter 14,15 , stabilization of either fast or slow non-conducting states of the channel 16,17 , gating charge immobilization [18][19][20] , and targeted uncoupling of channel gating from voltage-sensing 21 . Previous studies have shown that site-directed mutation of two strictly conserved aromatic residues in transmembrane segment 6 (S6) of the fourth sodium channel domain (DIV), Phe1760 and Tyr1767 in Na v 1.5, can virtually abolish channel inhibition by all classes of anti-arrhythmic drugs 12,[22][23][24] .…”
mentioning
confidence: 99%
“…VCF was first applied to skeletal muscle Na þ channels (Na V 1.4) and has been used to probe VSD interaction with inactivation (Cha et al, 1999a,b;Goldstein, 2013a, 2013b), local anesthetics (Arcisio- Miranda et al, 2010;Muroi and Chanda, 2009), and toxins (Campos et al, 2008(Campos et al, , 2007. To probe similar phenomena in the cardiac channel, we recently developed VCF protocols to track each of the VSDs of Na V 1.5.…”
Section: Cardiac Sodium Channel Na V 15mentioning
confidence: 99%